Importance Socio-Économique De Xylopia Aethiopica (Dun) A. Rich. Pour Les Populations Du Sud-Bénin - Ganglo, Caroline; Dan, Céline; Aoudji, Augustin K. N.; Gbetoho, Alain Jaures; Ganglo, Jean C. (European Scientific Journal, ESJ, 2017)
Xylopia aethiopica is a multi-purpose Non Timber Forest Product (NTFP) which products are consumed across Africa. This study aimed at generating useful information to support the sustainable management of Xylopia aethiopica in southern Benin. A survey was carried out to interview 122 stakeholders, including consumers and traders. Data were collected on the consumption of Xylopia aethiopica products, the income generated by their marketing, and the management the species trees by local people. As results, the species was mainly used in traditional medicine. Other forms of consumption included: spiritual rituals, fuelwood, food, and construction timber. Among Xylopia aethiopica products, the fruits were the most commercialized. The stakeholders operating in the commercialization system were: collectors, processors-wholesalers, and retailers. The gross margin per 100 kg of fruits averaged XOF 4500 for collectors and processors- wholesalers, and XOF 2500 for retailers. Xylopia aethiopica trees were privately managed based on land ownership. Given the decrease of the species, because of over-exploitation and cultural beliefs, the sensitizing of local people and the promotion of domestication are expected to support its conservation